Enhancing the wear properties of iron based powder metallurgy alloys by boron additions - BİLİCİ, MUSTAFA KEMAL; SALMAN, SERDAR; BOZKURT, YAHYA (ELSEVIER SCI LTD, 2007)
Wear behavior of iron based powder metallurgy (P/M) alloys with boron additions has been studied on a pin-on-disc wear tester using an alloy steel pin and disc of hardness 63 HRC. The P/M alloys in the as sintered as well as different conditions were investigated for their wear behavior. Wear rate was found to initially decrease with increase boron amount. Optical microscopy analysis method was preformed to characterize the basic microstructures for all samples. Scanning electron microscope observations of the worn surface revealed plastics deformations with delamination of surface layers by subsurface cracks as the mechanism in the as sintered conditions. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: STAINLESS-STEEL POWDER; DRY SLIDING WEAR; SINTERED IRON; BEHAVIOR; CR